Perceptions and Experiences of English Education Students in Learning IELTS through the IELTP Class - Sri Hastuti Novila Anggraini Saiful; Miftahul Jannah; Tuning Ridha Addhiny; Titik Agustina; Nurul Lailatul Khusniyah (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
In an increasingly globalized academic environment, English proficiency particularly through standardizedassessments like IELTS is essential for non-native speakers. This study explores the perceptions and experiences ofEnglish Education students at UIN Mataram enrolled in the IELTP (International English Language Test Preparation) class. The research addresses the challenges and benefits encountered by students in institutional IELTSpreparation programs, aiming to understand how they interpret and engage with the learning process. Using a qualitative descriptive approach, ten sixth-semester students were selected through purposive sampling and interviewed using semi-structured formats. Thematic analysis revealed consistently positive perceptions of theIELTP class, with students highlighting the clarity of instruction, authentic IELTS materials, and supportive classroom atmosphere. Despite varied motivations, ranging from pursuing postgraduate studies abroad to personal development, all students were highly engaged in the classroom. However, challenges such as large class size, internet instability, and test-focused intensity were noted. Participants suggested more interactive methods to balance the rigor of IELTS preparation. The findings suggest that the IELTS class should be well-facilitated; thus, itcan offer meaningful language learning experiences and foster professional growth for students, particularly for pre-service teachers. The study recommends incorporating learner-centered strategies and inclusive practices to improve program effectiveness.